DOCUMENTATION OF FOLK KNOWLEDGE ON WILD EDIBLE PLANTS OF RAMPACHODAVARAM AGENCY DIVISION, ANDHRA PRADESH, INDIA - Pampayya Thanthati1, Dr. S. Sandhya Rani2* (Chelonian Research Foundation, 2024)
Folklore medicinal uses of 23 species of Wild edible plants belonging to 21 genera of 20 families for various ailments among the tribes of Rampachodavaram or Rampa agency division of Alluri Sitharama Raju (ASR) district, Andhra Pradesh is reported along with local name, mode of administration and prescribed doses. Local people use leaves, stem, flowers, fruits, seeds and roots as a part of their diet. Present study reveals the importance of 23 species of plants as they are eaten substantially by village folk as well as by city dwellers. It is desirable to bring these plants under organized agriculture as new crops to increase their production and utilization. Keywords: Edible wild plants, Folk knowledge, Folk medicines, Tribal diet.